2008
DOI: 10.1590/s0102-86502008000400012
|View full text |Cite
|
Sign up to set email alerts
|

Indirect evaluation of estrogenic activity post heterotopic ovarian autograft in rats

Abstract: Purpose: To morphologically evaluate the estrogenic effect on the uterus and vagina of rats submitted to ovarian autografts. Methods: Twenty Wistar EPM-1 adult rats were bilaterally ovariectomized, followed by ovarian transplants in retroperitoneal regions. The animals were divided in four groups of five animals, according to the day of euthanasia: G4, G7, G14 and G21, corresponding to the 4th, 7th, 14th and 21st day after surgery, respectively. Vaginal smears were collected from the first day of surgery until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Experimental studies showed that the fall in number of follicles in grafted tissue due to hypoxia and delay re-vascularization occurs in two to four days [26]. The critical time for the full recovery of ovarian function after transplant happens during the first 24 hours [30]. Dissen et al showed profuse re-vascularization 48 hours after transplantation [31].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies showed that the fall in number of follicles in grafted tissue due to hypoxia and delay re-vascularization occurs in two to four days [26]. The critical time for the full recovery of ovarian function after transplant happens during the first 24 hours [30]. Dissen et al showed profuse re-vascularization 48 hours after transplantation [31].…”
Section: Discussionmentioning
confidence: 99%